5-Fluorouracil With Microneedling Modulates Wound Healing in a Murine Model: An Immunohistochemical Analysis of Mechanism and Dose Efficacy. Issue 6 (20th May 2022) - Homer, Natalie A.; Hanafy, Mahmoud S.; Baer, Susan C.; Watson, Alison H.; Somogyi, Marie; Shore, John W.; Blaydon, Sean; Durairaj, Vikram D.; Cui, Zhengrong; Nakra, Tanuj
Abstract : Purpose: The purpose of this study is to assess the dose-dependent immunohistopathological effects of intradermal microneedle-delivered 5-fluorouracil (5-FU) for postincisional wound healing in a murine model. Methods: A prospective experimental study was performed. Twelve hairless mice were randomized into 4 treatment groups for postincisional wound treatment: microneedling with topical saline, or microneeding with topically-applied 5-FU at concentrations of 25 mg/ml, 50 mg/ml, or 100 mg/ml. Two surgical wounds were created on each animal. Combination wound treatments were performed on postoperative days 14 and 28, and cutaneous biopsies were obtained on day 56. Specimens were analyzed by a dermatopathologist, blinded to the treatment group, for collagen thickness, lymphocytic infiltration, histiocytic response, sub-epidermal basement membrane zone thickness, and myofibroblast density. Results: Histopathologic evaluation showed increased collagen thickness, lymphocyte infiltration, and granuloma density in the groups undergoing microneedling treatment with 5-FU, compared to saline. Immunohistochemical analysis revealed a trend toward thicker basement membranes with higher concentrations of 5-FU used, reaching statistical significance between controls and those treated with 100 mg/ml 5-FU ( p = 0.0493). A trend toward decreasing myofibroblast density with increasing doses of 5-FU was noted. No postincisional or treatment complications were observed. Conclusions: Our results demonstrate that microneedling is an effective topical subepithelial drug delivery system, and further suggest a beneficial dose-dependent immunomodulatory effect of 5-FU on intermediate wound healing when used in combination with microneedling. We recommend a 5-FU dose at the mid-range 50 mg/ml concentration to simultaneously maximize efficacy and minimize complication risk. Abstract : Microneedle-delivered 5-Fluorouracil (5-FU) at a 50 mg/ml dose yields beneficial immunohistologic changes on postincisional wound healing in a murine model.